Public Policy and Inclusive Culture: A Vector of Convergence and the Search for Solutions for Accessibility of Cultural Goods - Zhanna V. Alekseeva; Elena A. Pakhomova; Egor O. Kazakov; Olga S. Tolmacheva; Mariya A. Yantarnaya (Observatory of Culture, 2026)
This article presents a comprehensive analysis of Russian state policy aimed at ensuring accessibility to culture for individuals with disabilities and limited health capabilities and their integration into the cultural life of society. Based on a detailed study of official reports from the Russian Ministry of Culture for 2022—2025, monitoring results from the Resource Educational and Methodological Center of the Russian State Specialized Academy of Arts, and federal statistical recods, the paper evaluates, the system of measures applied. The study focuses on the institutional mechanisms for coordinating state policy and the dynamics of infrastructural change in key types of cultural institutions — libraries, theaters, museums, and cultural and leisure facilities. The results of the federal projects “Accessible Environment” and “Cultural Environment” are analyzed in detail. The role of the “Pushkin Card” program as a tool for stimulating change is assessed. Regional practices for engaging cultural organizations in the rehabilitation and habilitation of individuals with disabilities are examined. Based on an analysis of data for the period 2022—2025, the measures taken are shown to be comprehensive and systemic. Their implementation has resulted in significant progress in creating physical, informational, and substantive accessibility to cultural goods for individuals with disabilities. This conclusion is supported by the sustained positive dynamics of key quantitative indicators over the four-year period.